The inclusion of insect meal from Hermetia illucens larvae in the diet of laying hens (Hy-line Brown) affects the caecal diversity of methanogenic archaea - Tiziana Maria Mahayri; Jakub Mrázek; Fulvia Bovera; Giovanni Piccolo; Giovanni Andrea Murgia; Giuseppe Moniello; Kateřina Olša Fliegerová (Poultry Science)
The effect of the dietary inclusion of Hermetia illucens larvae meal on the diversity of the methanogenic archaea in the caecum of laying hens (Hy-line Brown) was investigated using molecular methods. A total of 27 hens, selected equally for slaughter from 162 birds which were divided equally into 3 treatment groups including control group C with a diet containing corn-soybean meal and 2 experimental groups, HI25 and HI50, in which 25% and 50% of the soybean meal protein was replaced by the protein from a Hermetia illucens larvae meal, respectively. At 40 weeks of age, the methanogenic community of caecal content of 9 hens per group was analyzed using a 16S rRNA gene clone library. A total of 108 positive clones, 35 from the control group, 44 from the HI25 group and 29 from the HI50 group, were analyzed by Sanger sequencing. Methanomicrobiales, Methanobacteriales and Methanomassiliicoccales were the main orders found in groups C and HI25. Methanomassiliicoccales was absent in the HI50 group, which was dominated by the order Methanobacteriales. At the species level, Methanobrevibacter woesei was the most prevalent species in all three groups regardless of diet. Some species were found exclusively either in the control group (Methanogenic archaeon CH1270) or in the HI25 group (Methanorbis furvi strain Ag1). Methanogenic diversity was significantly lower in the HI50 group compared to the control and HI25 groups and Methanomassiliicoccaceae archaeon DOK was completely suppressed in HI50 group. Our preliminary results indicate that ingestion of Hermetia illucens larvae meal has considerable effect on the methanogenic community, promoting the abundance of Methanobrevibacter woesei and suppressing Methanomassiliicoccaceae archaeon DOK in the caeca of laying hens.